Optimization of a low wind speed horrizontal axis wind turbine generator system. - Chong , Chuong Leong (2011)
Most commercial wind turbines are designed for high wind speeds (>10m/s) making them inappropriate for use in most areas of South East Asia which are located in a low wind speed region. The purpose of this work is to optimize a small wind turbine and generator for lower wind speeds prevalent in Malaysia. An axial flux permanent magnet generator was designed and developed. This generator was optimized to achieve high power at low rotational speeds. The generator is capable of producing 200W of electrical power at a rotational speed of 300rpm. Wind turbine is investigated as a function of angle of attack and load on a 4.6 m diameter 3–blade horizontal axis wind turbine. The wooden blades used a NACA (National Advisory Committee for Aeronautics) 4415 profile. A total of 16 various combinations of load and attack angle were carried out. These tests were performed with the turbine mounted atop of the Mechanical Engineering building which is located in a representative low wind speed region. A data logger was used to collect power, temperature, wind speed and wind direction data. In a 2 month study, the average wind speed was 0.2m/s with peak power wind speed of 3m/s and a maximum wind speed recorded was 9 m/s. Average daily energy production of 150Wh was recorded. A 9 degree angle attack and 6 ohm load produced the maximum power of 200W at 4.2m/s wind speed. The coefficient of performance of the wind turbine was measured to be 0.27.